Potensi Bacillus sp. dalam Menghasilkan Indole Acetic Acid (IAA) serta Pengaruhnya Terhadap Panjang Akar Kecambah Benih Cabai Merah (Capsicum annuum L.) - Yulanda Saputri; Linda Advinda; Moralita Chatri; Dezi Handayani (Serambi Biologi, 2020)
Indole Acetic Acid (IAA) is a natural form of the auxin hormone found in plant roots and can stimulate plant growth. IAA functions to regulate physiological processes and stimulate plant growth such as cell lengthening and enlargement. Bacillus sp. including Plant Growth Promoting Rhizobacteria (PGPR) whose role is to increase the germination rate of red chili seeds (Capsicum annuum L.). This study aims to determine the ability of Bacillus sp. against the length of the root sprouts of red chili seeds (Capsicum annuum L.). This research was conducted in in August until November 2019 at the Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, State University of Padang. The method used is descriptive and quantitative experiments. The results obtained showed that the isolate Bacillus sp. able to produce IAA and administration of isolates Bacillus sp. significant effect on root length of the red chili sprouts. Keywords : Indole Acetic Acid (IAA), Bacillus sp.